2014
DOI: 10.1115/1.4026084
|View full text |Cite
|
Sign up to set email alerts
|

“Adult” Robot Enabled Learning Process in High Precision Assembly Automation

Abstract: Typical robot teaching performed by operators in industrial robot applications increases the operational cost and reduces the manufacturing efficiency. In this paper, an "adult" robot enabled learning method is proposed to solve such teaching problem. This method uses an "adult" robot with advanced sensing and decision-making capabilities to teach "child" robots in manufacturing automation. A Markov Decision Process (MDP) which aims to correct the "child" robot's tool position is formulated and solved using Q-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Very few papers have reported the development of DSS for automating actual manufacturing processes such as machining, assembly and inspections. [10][11][12] For example, Tapoglou et al 17 have developed a cloudbased multi-objective optimisation solution for selecting the machining parameters based on real-time monitoring of the part. Makris et al 18 have developed an algorithm for deciding the sequence of instructions to be shown for assembly support based on the given assembly sequence, semantic classification of the subprocesses and components and the real-time task flow.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few papers have reported the development of DSS for automating actual manufacturing processes such as machining, assembly and inspections. [10][11][12] For example, Tapoglou et al 17 have developed a cloudbased multi-objective optimisation solution for selecting the machining parameters based on real-time monitoring of the part. Makris et al 18 have developed an algorithm for deciding the sequence of instructions to be shown for assembly support based on the given assembly sequence, semantic classification of the subprocesses and components and the real-time task flow.…”
Section: Related Researchmentioning
confidence: 99%
“…Such systems have been proposed and developed for various applications in manufacturing. Cheng and Chen 10 used the Markov decision process (MDP) that allows one robot to teach a task to another robot in an effort to automate production using a Markov-based decision-making process. However, the Markov assumption means that the next system state depends only on the previous system state without any feed forward to assist in decision-making.…”
Section: Related Researchmentioning
confidence: 99%
“…[1]- [3]). Reinforcement learn- * corresponding author Email addresses: mgaeta@unisa.it (Matteo Gaeta), loia@unisa.it (Vincenzo Loia), semiranda@unisa.it (Sergio Miranda), stomasiello@unisa.it (Stefania Tomasiello ) A C C E P T E D M A N U S C R I P T ing algorithms compute control policies by means of an agent, who can learn directly on the system (on-line control) or from an interaction with a simulator of the system (off-line or batch control).…”
Section: Introductionmentioning
confidence: 95%
“…However, the way of the tool center point (TCP) moved from initial pose to contact the hole plate which was not involved. Cheng solved peg-in-hole positioning process by Q-Learning (Cheng and Chen, 2014). After Q-Learning training, the TCP of the robot can move in a ladder-like line from initial pose to the target hole.…”
Section: Introductionmentioning
confidence: 99%